KNOW-Ped CKD (KoreaN cohort study for outcomes in patients with pediatric CKD): Design and methods. Issue 1 (December 2016) - Kang, Hee; Choi, Hyun; Han, Kyung; Kim, Seong; Cho, Hee; Cho, Min; Shin, Jae; Lee, Joo; Lee, Joongyub; Oh, Kook; Park, Young; Cheong, Hae; et al.
Abstract Background The global prevalence of chronic kidney disease (CKD) is increasing. In children, CKD exhibits unique etiologies and can have serious impacts on children's growth and development. Therefore, an aggressive approach to preventing the progression of CKD and its complications is imperative. To improve the understanding and management of Asian pediatric patients with CKD, we designed and launched KNOW-Ped CKD (KoreaN cohort study for Outcome in patients With Pediatric Chronic Kidney Disease), a nationwide, prospective, and observational cohort study of pediatric CKD with funding from the Korean government. Methods/design From seven major centers, 450 patients <20 years of age with CKD stages I to V are recruited for the comprehensive assessment of clinical findings, structured follow-up, and bio-specimen collection. The primary endpoints include CKD progression, defined as a decline of estimated glomerular filtration rate by 50 %, and a requirement for renal replacement therapy or death. The secondary outcomes include the development of left ventricular hypertrophy or hypertension, impairment of growth, neuropsychological status, behavioral status, kidney growth, and quality of life. Discussion With this study, we expect to obtain more information on pediatric CKD, which can be translated to better management for the patients. Trial registration NCT02165878 (ClinicalTrials.gov), submitted on June 11, 2014.